Westica online ordering system via SMS notification / Nurul Rashikin Mat Nen - Mat Nen, Nurul Rashikin (2008)
This project was prepared according to the design and implementation of a web-based system for online ordering with the ability to view the product and makes the order. It is known as Westica Online Ordering System via SMS Notifications. Online ordering encompasses all the activities a business conducts via World Wide Web with the aim to attract new business, retain current business and develop its brand identity. This project will emphasize to view the online catalogue anytime, whether it's adding new product or adjusting price without the expense and time of traditional print catalogue. This system will also help the customers of Westica Company to make order online.The SMS notification will send to the new customers to inform their usernames and password for next action and also to advertise the new products to the current customers through SMS. The reason of why the researcher use SMS notification rather than email because the information can transmit more faster and efficient. The methodology approach used in this project was Iterative Development which is consists of five phases that are planning, data analysis, design, development and testing. This system was developed using PHP programming language, PhpMyAdmin as database, WAMP, Ozeki as a SMS server, mobile phone as a GSM device and a notebook. This system is running on Windows XP Professional operating system.